1996
DOI: 10.1017/s0043174500094352
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Factors Affecting Germination of Tropical Soda Apple (Solanum viarum)

Abstract: Laboratory studies were conducted to determine the effect of various factors on germination of tropical soda apple. Tropical soda apple seed were found to be moderately photoblastic with 30% germination occurring in the dark. Germination increased in response to green (545 nm) and red light (650 nm) to 75 and 66%, respectively, indicating phytochrome regulation. No germination occurred in response to blue (450 nm) and far-red light (750 nm). Germination increased from 4 to 64% between 10 to 30 C, but no germin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0
3

Year Published

1997
1997
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 11 publications
2
32
0
3
Order By: Relevance
“…These patterns are similar to the trends observed in other invasive weeds, namely Crofton Weed ( Eupatorium adenophorum ) (Lu et al . 2006), Solanum viarum (Akanda et al . 1996) and Jubatagrass ( Cortaderia jubata ) (Drewitz & DiTomaso 2004), which all showed higher germination when exposed to a 12‐h photoperiod than to continuous darkness.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These patterns are similar to the trends observed in other invasive weeds, namely Crofton Weed ( Eupatorium adenophorum ) (Lu et al . 2006), Solanum viarum (Akanda et al . 1996) and Jubatagrass ( Cortaderia jubata ) (Drewitz & DiTomaso 2004), which all showed higher germination when exposed to a 12‐h photoperiod than to continuous darkness.…”
Section: Resultsmentioning
confidence: 99%
“…These patterns appear to show the evolution of ecotypes adapting to the different temperature regimes experienced at the three locations, with the temperate site not only encountering the lowest overall temperatures, but also the greatest variation with hot, dry summers. The very broad range of temperatures under which common ragweed germinates corresponds with the wide distribution of the species in China (Zeng 2003), and is again reflected by other successful invasive weeds, such as Cortaderia jubata (8–35°C) (Drewitz & DiTomaso 2004), Solanum viarum (10–35°C) (Akanda et al . 1996) and Pueraria lobata (Susko et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most relevant to our research, Al-Wakeel and Hamed (26) showed more growth suppression under 'yellow' (peak output at 595 nm) than 'green' (peak output at 520 nm) light in cucumbers. Even recent studies claiming 'green' or 'yellow' light responses use unequal photosynthetic photon fluxes (26,27), do not provide sources with clean cut-off and therefore vary wavelengths other than 'green' (27), or fail to report complete spectral outputs from their lamp and filter sources (26,(28)(29)(30).…”
Section: 'Yellow' Wavelengthsmentioning
confidence: 99%
“…Akanda et al, 1996;Gan et al, 1996). Although some of the models give a good fit to the data, this paper describes a model with parameters which have clearer biological meanings.…”
Section: Discussionmentioning
confidence: 99%